Knowledge and attitude towards family planning practices among non-acceptors in a rural area in Bangalore, India - S., Hemavarneshwari; S., Mangala; G., Subrahmanyam (International Journal of Research in Medical Sciences, 2017)
Background: India became the first country in the country to launch a National family planning programme in 1952. Population explosion is still a prime problem in the country. The rate of contraceptive use is 40.4% in 2011 which is far below the National goal of Couple protection rate of 60% by 2000 A.D. The present study was carried out in a rural area, Bangalore, India. The objective of the study was to assess the knowledge and attitude towards family planning practices among non-acceptors and to find out the factors associated with non-acceptance of family planning among married women in the rural field practice area of Vydehi Institute of Medical Sciences and Research Centre, Bangalore, India. Methods: A cross sectional study was carried out in the rural field practice area. Out of 33 villages in the rural health centre area, a total of 6 villages were selected and using cluster sampling method 235 eligible couples who were not using contraceptives were included in the study. A semi- structured questionnaire was used to collect the data during house to house visits from August to October 2012. Results: Among the 235 eligible couples, 218(92.7%) had knowledge about contraception and it was significantly associated with the level of literacy (p<0.01). Reasons for non-acceptance of family planning were male child preference (26.8%), fear of side effects (14%), fear of surgery and female child preference (10.6%), opposition of partner (7.2%). Conclusions: Most common reason for non-acceptance of family planning was male child preference (26.8%). There is a need for behaviour change communication for eligible couples regarding family planning adoption among the non-acceptors highlighting the importance of small family, happy family.